2011
DOI: 10.1007/s00170-011-3648-0
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid-constrained MOGA and local search method to optimize the load path for tube hydroforming

Abstract: The production of a tubular hydroformed part often requires a combination of internal pressure and axial force at the tube ends to fully form the tube to its specified geometry. A successful hydroforming process requires not only achieving a part that conforms to the design specifications, but also ensures that the part has a reasonably uniform thickness distribution and is free of defects, such as wrinkles, severe thinning, or fractures. The load path design (pressure vs. end feed history) largely determines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors experienced the application of dual RBF for multi-objective robust optimization and the use of adaptive RBF to optimize the loading path for T-shape THF process [32,33]. An [34,35] used KRG to accelerate calculation speed in multi-objective optimization in THF process. Ingarao et al [36] provided a comparison between three surrogate models, namely RSM, moving least squares approximation, and KRG model, to design a THF process.…”
Section: Introductionmentioning
confidence: 99%
“…The authors experienced the application of dual RBF for multi-objective robust optimization and the use of adaptive RBF to optimize the loading path for T-shape THF process [32,33]. An [34,35] used KRG to accelerate calculation speed in multi-objective optimization in THF process. Ingarao et al [36] provided a comparison between three surrogate models, namely RSM, moving least squares approximation, and KRG model, to design a THF process.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the single-objective optimization problem, the fundamental difference from the multi-objective genetic algorithm (MOGA) is that its result is a set of optimum solutions rather than simply a unique solution; we call this set of optimal solutions the Pareto optimal sets, 20 and any solution within the Pareto optimal sets is a feasible design…”
Section: Optimizationmentioning
confidence: 99%
“…Ben and EI [15] provided a deep comparison between the quadratic polynomial response surface (RS) model and radial basis function (RBF) as surrogate techniques to construct surrogate models for global sensitivities and multi-objective optimization of the THF process, and they found that the RBF showed its superiority over the quadratic polynomial RS model to deal with nonlinearities proved through analytical test function and practical THF process. An et al [16][17][18] used a multi-objective optimization algorithm combined with design of experiment (DOE) and FEM to determine the optimal loading path in the THF process. Kadkhodayan and Moghadam [19,20] established a new method to optimize the loading parameters in the T-, X-, Y-shape THF process based on Taguchi method and the RS model.…”
Section: Introductionmentioning
confidence: 99%